E-LEARNING-BASED TRAINING MODEL FOR ACCOUNTING TEACHERS - Endang Sri Andayani; Sawitri Dwi Prastiti; Ika Putri Larasati (Universitas Negeri Malang, 2015)
Abstract: E-Learning-Based Training Model for Accounting Teachers. To improve the competencies of teachers located on remote and diverse areas, it is viable and commendable to implement e-learning-based training. In view of this purpose, the present action research examines the effectiveness of e-learning-based training for accounting teachers. The findings reveal that teachers with poor ICT skills need to take orientation around online class first in order to get familiar with the use of ICT for learning purposes. Meanwhile, teachers with good ICT skills are able to engage directly in the training. The research project also shows that the effectiveness of training can be achieved through sequentially organized materials and accessed through the learning progress of the trainees. Encouragement to the trainees for active involvement in the discussion forums during the training results in high final scores at the end of the training session. Keywords: E-learning, teacher training, accounting, East Java Abstrak: Model Pelatihan Berbasis E-Learning bagi Guru Akunting. Program pengembangan professional bagi para guru merupakan agenda utama untuk meningkatkan kualitas pendidikan. Untuk meningkatkan kompetensi guru, implementasi pelatihan berbasis e-learning dimungkinkan untuk menjangkau para guru yang berasal dari berbagai wilayah terpencil. Penelitian tindakan ini menguji efektivitas pelatihan berbasis e-learning pada guru-guru akuntansi di Jawa Timur. Temuan penelitian mengungkap bahwa para guru yang memiliki kecakapan ICT rendah harus mengambil pelatihan orientasi pembelajaran online terlebih dahulu agar akrab dengan penggunaan ICT untuk tujuan-tujuan pembelajaran. Sedangkan para guru yang sudah memiliki kecakapan ICT memadai dapat langsung mengikuti pelatihan. Efektivias pelatihan dapat dicapai dengan cara mengorganisasikan materi pelatihan secara berurutan dan hanya dapat diakses sesuai dengan kemajuan belajar peserta pelatihan. Dorongan partisipasi bagi peserta untuk terlibat aktif dalam forum diskusi menghasilkan nilai akhir yang tinggi pada akhir pelatihan. Kata kunci: E-learning, pelatihan guru, akuntansi, Jawa Timur